2020
DOI: 10.48550/arxiv.2012.00560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quick and Robust Feature Selection: the Strength of Energy-efficient Sparse Training for Autoencoders

Abstract: Major complications arise from the recent increase in the amount of highdimensional data, including high computational costs and memory requirements. Feature selection, which identifies the most relevant and informative attributes of a dataset, has been introduced as a solution to this problem. Most of the existing feature selection methods are computationally inefficient; inefficient algorithms lead to high energy consumption, which is not desirable for devices with limited computational and energy resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, pruning plasticity drops significantly after the second learning rate decay, leading to a situation where the pruned networks can not recover from the continued training. This finding helps to explain several observations (1) for gradual magnitude pruning (GMP), it is always optimal to end pruning before the second learning rate drop [73,13]; (2) dynamic sparse training (DST) benefits from a monotonically decreasing pruning rate with cosine or linear update schedule [8,9];…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, pruning plasticity drops significantly after the second learning rate decay, leading to a situation where the pruned networks can not recover from the continued training. This finding helps to explain several observations (1) for gradual magnitude pruning (GMP), it is always optimal to end pruning before the second learning rate drop [73,13]; (2) dynamic sparse training (DST) benefits from a monotonically decreasing pruning rate with cosine or linear update schedule [8,9];…”
Section: Introductionmentioning
confidence: 68%
“…Our paper re-emphasizes the great potential of during-training pruning in reducing the training/inference resources required by ML models without sacrificing accuracy. It has a significant environmental impact on reducing the energy cost of the ML models and CO2 emissions [1,52,15,55,60]. Pruning rate=0.2 Pruning rate=0.5 Pruning rate=0.9 Pruning rate=0.98…”
Section: Conclusion and Reflection Of Broader Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic sparse training has emerged and showed its success in many other fields as well [21,36]. Atashgahi et al [3] adopted the SET algorithm for feature selection and showed its robustness for very high dimensional data. Zhu et al [59] proposed a modified version of the SET algorithm for federated learning.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the previous efforts in this direction show the effectiveness of DST in outperforming dense neural networks with high sparsity levels in supervised classification tasks [37,40,7]. Recently, DST showed its success in other domains such as text classification [32], feature selection [3], continual lifelong learning [48], and federated learning [59].…”
Section: Introductionmentioning
confidence: 99%